Tantangan dan Kesiapan Indonesia Menghadapi Ancaman Siber - Megasari, Intan Indah; Humaira Azzahra, Yasmin (Citizenship Education, Faculty of Education, Jambi University, 2025)
This research aims to raise awareness and take concrete steps so that Indonesia can improve its readiness to deal with cyber threats and protect national security in the digital era. The research method used is a literature study reviewing various sources, such as scientific articles, research reports, government policies, mass media news, and other publications relevant to the research topic. The data collected was analyzed qualitatively to identify key themes related to Indonesia's challenges and readiness in facing cyber threats. The results showed that Indonesia faces various significant challenges in dealing with cyber threats, including gaps in the capacity of competent and trained experts, lack of awareness of cyber attacks, weak coordination between government agencies and the private sector in handling cyber threats that still need to be improved, limited budget allocated for cyber security is still limited, and regulations that are not yet strong related to cyber security in technological developments